Mapping Heaven’s Influence: Morality, Mental Health, and Economic Impacts of Afterlife Beliefs - Pangaribuan, Hisar; Sunarsi, Denok; Sihombing, Jenny; Winarno, Wing Wahyu (Universitas Negeri Makassar, 2025)
The concept of heaven plays a pivotal role within religiosity, acting as both a metaphysical endpoint and an ethical guide, profoundly influencing personal beliefs and societal structures. This study aims to examine the interplay between belief in heaven and its influence on moral decision-making, psychological well-being, and economic productivity across diverse contexts. Employing a systematic literature review, this research involved a bibliometric analysis of 427 publications from Scopus (2005–2024) using VOSviewer to identify clusters and emerging trends. Through co-occurrence mapping, the study isolated five primary research clusters, including moral behavior, psychological impacts, cultural influences, economic implications, and demographic variables. Key findings reveal that belief in heaven correlates with both conservative moral perspectives and increased psychological resilience, with notable demographic differences. Economic implications suggest that afterlife beliefs support values like honesty and thrift, indirectly boosting economic productivity. The study underscores the distinct role of heaven as an isolated concept within religiosity, contributing novel insights into the broader societal impact of afterlife beliefs. Findings have practical implications for policymakers, religious leaders, and educators in leveraging heaven’s moral framework to foster pro-social behavior and societal well-being across culturally diverse populations.